Sulphate-based electrochemical processes as an alternative for the remediation of a beauty salon effluent‡ - Vieira, Gleilson de França; Barbosa Segundo, Inalmar D.; Souza, Domingos F.S.; Gondim, Amanda D.; Cavalcanti, Lívia N.; dos Santos, Elisama V. [UNESP]; Martínez-Huitle, Carlos A. [UNESP] (Elsevier, 2024)
Beauty salons (BS) are places that deal with a wide range of cosmetics with potentially hazardous chemicals, and their effluent should be properly treated before going to the sewage system, once it represents characteristics of industrial wastewater. This work provides an extensive characterization of a BS effluent and its respective electrochemical treatment by comparing NaCl, Na2SO4, and Na2S2O8 as supporting electrolytes with a boron-doped diamond (BDD) as anode, applying 10 or 30 mA cm−2 of current density (j). The inclusion of UVC irradiation was also performed but the improvements achieved in removing the organic matter were null or lower. The analysis of chemical oxygen demand (COD) removal, energy consumption, and total current efficiency (TCE) was required to prove the efficacy of the processes and the comparative study of the performance of different technologies. Precipitate analysis was also done due to the high turbidity of the raw effluent and the appearance of a precipitate before and during the electrolysis, mainly with Na2S2O8. The precipitate confirmed the presence of silicates and small amounts of heavy metals. The results clearly showed that 6 h of treatment with Na2SO4 achieved 58% of COD removal with an energy consumption of about 0.52 kWh m−3, being the best electrolyte option for treating BS effluent by applying 10 mA cm−2. Under these experimental conditions, the final wastewater can be directly discharged into the sewage system with a lower amount of visible precipitate, and with 73% less turbidity. The treatment here proposed can be used as an alternative to decision-makers and governments once it can be a step further in the implementation of better and advanced politics of water sanitation.
Keywords: BDD; Diamond electrode; Persulphate; PPCPs; Precipitates analysis